Geely motors: a Chinese automaker enters international markets. (21st August 2008) - Alon, Ilan; Fetscherin, Marc; Sardy, Marc
On 22 January 2006, Shufu Li, the Director of International Marketing for Geely Motors, was rushing to the check-in counter at the Detroit Metropolitan Airport in order to travel back to Shanghai, China. He had just come from the Detroit International Auto Show where his company had presented its new car models. Geely (pronounced 'Gee-Lee') had been selling cars in China since 1997. In 2004, they had begun exporting cars to North Africa and Latin America. Geely had now set their sights on the USA, the largest automobile market in the world. Geely's management was planning to sell cars in the US market for under US$10, 000 by late 2008. The International Auto Show in Detroit was crucial in order to get feedback from and establish relationships with potential business partners, customers and the press. While he was boarding the plane, Mr. Li began to reflect on Geely's transition from a regional manufacturer focused on the domestic Chinese market to an international player. Would the last few years of their marketing effort turn Geely into a global player in the auto market? Would US consumers warm to the cars Geely had shown at the auto show? How could Geely overcome the lack of brand name and the negative country-of-origin quality image that Chinese manufacturers have?